Implikasi Perjanjian Kawin Terhadap Harta Dalam Perkawinan Campur - Situmeang, Paima (Recital Review, 2019)
This is a research study that examines the implications of the agreement on marriage to assets in mixed marriages. The problems raised in this study discuss how the form of legal protection for couples who are married in mixed marriages and what are the legal consequences of the agreement to marry property in mixed marriages. This study uses normative methods with steps of description, systematization and explanation of the contents of positive law in depth using conceptual approaches, legal approaches and systematic synchronization analysis. The results of the study indicate that legal protection of property in the marriage agreement can only be carried out during the marriage. Where the marriage agreement is a law for the parties, this is in accordance with article 1338 of the Civil Code. According to the provisions of Article 29 of the Marriage Law the contents of the agreement must be carried out in good faith by taking into account the provisions of the law, the norms of decency and public order. The authority and responsibility of the notary in making the marriage agreement deed made is limited to the contents of the agreement that has fulfilled the legal requirements of the agreement based on article 1320 of the Civil Code. The legal consequences of a marriage agreement that has been ratified by a marriage / marriage registrar employee are binding and apply as a law to the parties and third parties to the extent that the party is involved. Article 1338 of the Civil Code states that all agreements made legally apply as laws for those who make them. The agreements are irrevocable other than by agreeing with both parties, or for reasons which are deemed sufficient by law, agreements must be carried out in good faith. If one of the parties does not implement the marriage agreement and harms the other party, compensation for the party who feels the loss is requested to the court, both demands regarding the implementation of the agreement and compensation claims. Therefore the most important meaning of the marriage agreement must be carried out in good faith and obedience, because the marriage agreement made has legal consequences for the assets in a mixed marriage.